Positron emission tomography (PET) imaging of nicotine-induced dopamine release in squirrel monkeys using [18F]Fallypride - Naylor, Jennifer E.; Hiranita, Takato; Matazel, Katelin S.; Zhang, Xuan; Paule, Merle G.; Goodwin, Amy K. (Drug and alcohol dependence, 2017)
•Study of the effects of nicotine on dopamine (DA) D2/D3 receptors in squirrel monkey brains.•Nicotine administration resulted in ligand uptake across brain regions.•Tobacco products containing nicotine may cause alterations to the DA system. Nicotine, the principal psychoactive tobacco constituent, is thought to produce its reinforcing effects via actions within the mesolimbic dopamine (DA) system. The objective of the current study was to examine the effect of nicotine on DA D2/D3 receptor availability in the nonhuman primate brain with the use of the radioligand [18F]fallypride and positron emission tomography (PET). Ten adult male squirrel monkeys were used in the current study. Each subject underwent two PET scans, one with an injection (IV) of saline and subsequently one with an injection of nicotine (0.032mg/kg). The DA D2/D3 antagonist, [18F]fallypride, was delivered IV at the beginning of each scan, and nicotine or saline was delivered at 45min into the scan. Regions of interest (ROI) were drawn on specific brain regions and these were used to quantify standard uptake values (SUVs). The SUV is defined as the average concentration of radioactivity in the ROI x body weight/injected dose. Using the cerebellum as a reference region, SUV ratios (SUVROI/SUVcerebellum) were calculated to compare saline and nicotine effects in each ROI. Two-way repeated ANOVA revealed a significant decrease of SUV ratios in both striatal and extrastriatal regions following an injection of nicotine during the PET scans. Like other drugs of abuse, these results indicate that nicotine administration may produce DA release, as suggested by the decrease in [18F]fallypride signal in striatal regions. These findings from a nonhuman primate model provide further evidence that the mesolimbic DA system is affected by the use of products that contain nicotine.